AKIBAT HUKUM ATAS PUTUSAN PAILIT BAGI DEBITOR TERHADAP KREDITOR PEMEGANG HAK JAMINAN FIDUSIA - TUAH BANGUN (PREMISE LAW JURNAL, 2015)
UUJF which determines the guarantee of fiduciary collateral gives specific position for a certain creditor on other creditors. However, UUK (Law on Bankruptcy) states that although a creditor who holds fiduciary collateral treats the object of fiduciary collateral as if there were no bankruptcy in the debtor, there is a regulation which states that there is a stay of the fiduciary collateral in boedel bankruptcy status. Therefore, there are some problems about legal provisions on the implementation of creditor’s bankruptcy as the holder of fiduciary collateral on the debtor as the giver of fiduciary collateral, creditor’s position as the holder of fiduciary collateral which has been burdened by the fiduciary collateral when the debtor goes bankrupt, and the legal consequence for the creditor as the holder of fiduciary collateral in executing fiduciary collateral given to the debtor who has gone bankrupt. The type of the research was judicial normative by studying legal norms and other legal provisions related to fiduciary collateral institution and other bankruptcy institutions in Indonesia, and the source of data were obtained from by library study. Keywords: Legal Consequence on the Ruling of Bankruptcy, Holder of Fiduciary Collateral